2015
DOI: 10.1016/j.dib.2015.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Data in support of substrate flexibility of a mutated acyltransferase domain and implications for polyketide biosynthesis

Abstract: Enzyme-directed mutasynthesis is an emerging strategy for the targeted derivatization of natural products. Here, data on the synthesis of malonic acid derivatives for feeding studies in Saccharopolyspora erythraea , the mutagenesis of DEBS and bioanalytical data on the experimental investigation of studies on the biosynthetic pathway towards erythromycin are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In other studies, the prototypical PKS (DEBS) was subjected to mutagenesis and the generated active site-mutant library was screened for substrate selectivity [ 61 , 63 , 64 , 65 ]. Several single amino acid substitutions, having an impact on the selectivity of the PKS, were identified.…”
Section: Strategies Of Acyltransferase-based Polyketide Engineerinmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, the prototypical PKS (DEBS) was subjected to mutagenesis and the generated active site-mutant library was screened for substrate selectivity [ 61 , 63 , 64 , 65 ]. Several single amino acid substitutions, having an impact on the selectivity of the PKS, were identified.…”
Section: Strategies Of Acyltransferase-based Polyketide Engineerinmentioning
confidence: 99%
“…Bravo-Rodriguez et al used a combined approach, which involved molecular modelling and mutagenesis of the AT6 of DEBS and showed that the V295A mutation of this AT leads to a wider active site and improves the promiscuity for non-native substrates [ 61 , 63 , 64 ].…”
Section: Strategies Of Acyltransferase-based Polyketide Engineerinmentioning
confidence: 99%